PORTECT: Porcine detection kit using CRISPR-CAS method as new innovation for rapid and accurate halal detection - Saputra, Rafi Irsyad; Tiftazani, Feyza; Larasati, Rifa Cansa; Sembiring, Indra Refipal (IPB University, 2025)
The PORTECT Porcine Detection Kit is an innovative solution leveraging CRISPR-Cas technology for rapid and accurate detection of porcine DNA in food products, addressing the growing demand for halal certification. This system uses a guide RNA (gRNA) designed specifically to recognize and target porcine DNA sequences, triggering Cas12 enzymes to cleave the DNA and a reporter compound for a visual color change. This process allows for precise, fast, and efficient detection of non-halal substances. Unlike traditional methods like PCR and ELISA, which require complex procedures, the PORTECT kit offers a more accessible and time-saving approach to halal verification, ensuring consumer trust and regulatory compliance. The technology is developed with bioinformatics tools and produces highly specific gRNA to target the porcine gene. The kit demonstrates significant potential in both the halal food industry and the general market for DNA detection tools, but future developments aim to lower production costs and expand detection capabilities beyond porcine DNA.